Transceiver and system design for digital communications - Bullock, Scott R., 1950- (IET telecommunications series ;, 2017)
In this 5th Edition, the author continues to evaluate various novel techniques and design methods for the modulation and transmission of digital data, allowing the readers to gain a firm understanding of the processes needed to effectively design wireless data link communication systems.